Bridging policy and practice: Malaysia charts a value-based future in healthcare - Choon, June Wai Yee (Faculty of Pharmacy, 2025)
In a landmark gathering held on 9th July 2025, the Ministry of Health (MOH) and the Pharmaceutical Association of Malaysia (PhAMA) brought together leading minds across government, academia, and industry for the Value-Based Healthcare (VBHC) Conference 2025. Themed “Outcomes that Matter, Access that Delivers,” the conference sought to move Malaysia’s health system toward a more sustainable, patient-centric model—where value, not volume, drives investment and care.